2023
DOI: 10.1186/s40798-023-00563-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Football Injuries of the German Bundesliga: A Media-Based, Prospective Analysis over 7 Consecutive Seasons

Abstract: Background This study describes the implementation of a standardised, prospective injury database covering the entire 1st male German football league (“Bundesliga”) based on publicly available media data. For the first time, various media sources were used simultaneously as the external validity of media-generated data was low in the past compared to data obtained by way of the “gold standard”, i.e. by the teams’ medical staffs. Methods The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
10
0
2
Order By: Relevance
“…Severe injuries accounted for 21–37% of all injuries,1 3 or 0.78 injuries per 1000 hours 6. This aligns with injury locations and injury severity reported in adult professional football players 6–8…”
Section: Introductionsupporting
confidence: 71%
“…Severe injuries accounted for 21–37% of all injuries,1 3 or 0.78 injuries per 1000 hours 6. This aligns with injury locations and injury severity reported in adult professional football players 6–8…”
Section: Introductionsupporting
confidence: 71%
“…This study reported a rate of 46.66 injuries per year, which represents a difference of 35.55% concerning our study. 3 Árnason et al 8 evaluated 10 elite Icelandic football clubs, and 82% of the injuries occurred in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…7 Em um estudo alemão que avaliou atletas da Bundesliga (liga alemã de futebol profissional) nas temporadas de 2008 a 2014, foram observados 280 episódios de entorses do tornozelo (5,17% do total de lesões) com uma taxa de 46,66 lesões por ano, o que representa uma diferença de 35,55% em relação ao nosso estudo. 3 Árnason et al 8 avaliaram 10 clubes da elite do futebol islandês, e do total de lesões encontradas, 82% localizavam-se nos membros inferiores.…”
Section: Discussionunclassified
See 2 more Smart Citations